A precise prediction of the tooth root stresses for involute external gears with any fillet geometry under consideration of the exact meshing condition. (November 2019) - Paucker, Tobias; Otto, Michael; Stahl, Karsten
An environmentally friendly design of gearboxes means to increase the utilization of material steadily. This leads to in many ways optimized constructions, which require an exact prediction of occurring stresses under given load-carrying capacity to guarantee sufficient endurance. This paper shows a very precise method to calculate the occurring tooth root stress for involute, external gearings with any form of fillets within a few seconds. A two-dimensional Boundary–Element–Model is used to receive the notch stresses of the fillets which are linked to a high quality analytical tooth contact analysis to consider the exact relations of the gear meshing. The introduced model also allows a calculation of the occurring tension and compression stresses along the whole fillet for different meshing positions. This paper shows the optimization potential by using the described method in comparison to a standard approach.